Behavioral Policies and Teen Traffic Safety - Dee, Thomas S; Evans, William N (American Economic Review, 2001)
Traffic fatalities are the leading cause of death among teens and young adults, accounting for one-third of all deaths among those 15–20 years of age. The large share of teen mortality attributed to car travel is not entirely unexpected. Driving is an inherently risky activity, and teens rarely die of other nonviolent causes. However, teens also face levels of traffic-related risk that are substantially higher than those of older, more experienced drivers. For example, the teen traffic fatality rate (defined as deaths of 16–19-year-olds per population) is nearly double the rate for adults aged 25 and older. Since teens drive less than adults, this ratio increases to nearly 2.5 when denominated by miles of travel. While these are sobering numbers, teen traffic safety has improved considerably over the past 20 years. Since 1979, the teen traffic fatality rate has fallen by 37 percent. Much of this drop occurred in the 1986–1992 period when rates fell 25 percent. These decreases in teen fatality rates are much larger than the contemporaneous changes for adults aged 25 and older, whose fatality rates fell by 22 percent in the 1979–1997 period, and by 13 percent over the 1986–1992 time frame. The relative improvements of teens are even more impressive when one considers that they have become increasingly dependent on the automobile. Between 1983 and 1995, vehicle miles traveled by teens aged 16–19 nearly doubled. When denominated by vehicle miles traveled, teen fatality rates have fallen by 50 percent since 1983. The gains in teen traffic safety are likely to reflect a number of causes. For example, over this period, there were several advances in car crash-worthiness (e.g., improved designs, increased car weight, the introduction of air bags). However, these improvements also appear to reflect a reduction in risk-taking behind the wheel, in particular, increases in seat-belt use and reductions in drunk driving. In this study, we present some evidence on the efficacy of key state policies in promoting these gains by discussing reduced-form models of traffic fatalities. We also consider whether the life-saving effects of an important policy, minimum legal drinking ages, have been attenuated by a possible shift of alcohol-related traffic risks to young adulthood.